THEMATIC STUDY OF QURANIC VERSES ON LEADERSHIP AND MANAGEMENT - Loso Judijanto; Muh Syamsul Arifin; Abdul Wahab Syakhrani (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
A thematic study of Quranic verses on leadership and management reveals how Islam emphasizes leadership that is just, integrity, and service, where leaders are not only expected to achieve organizational goals but are also responsible for the well-being and growth of individuals in their communities. Quranic verses, such as in Surah Al-Baqarah and Surah Sad, provide guidance on ethical and transformative leadership values, supporting the establishment of leadership models that prioritize moral and spiritual aspects in management practices and contemporary organizational strategies. The study in this research uses the literature research method. The results show that Islam emphasizes leadership roles that not only prioritize goal achievement and performance, but also pay great attention to justice, integrity, and service to the community. The findings open new insights into the concepts of transformative and servant leadership, and offer the view that leadership in Islam includes strong moral and spiritual aspects. The implications of these findings are not only relevant for leadership and management theory, but also for organizational practices that seek to integrate ethical and spiritual values in their daily activities